PROPOSED ADDITIONAL HEALTH INSURANCE SCHEME AS SUPPLEMENTARY EMPLOYEE BENEFIT : CASE STUDY FOR PUBLIC SERVANTS IN INDONESIA - Isyana Deviprameswari (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
Access to health care has been a constant concern in developing countries due to inequitable distribution. As demonstrated in industrialized nations with reassuring outcomes, insurance is a true instrument for mitigating these issues. In order to address this issue, Indonesia implemented the BPJS Kesehatan national health insurance plan. Acceptance and contentment with the BPJS Kesehatan, on the other hand, are impediments to the attainment of its goals. The study's goal is to measure the level of acceptability and satisfaction with Indonesia's national health insurance program among public servants in the Ministry of Finance. A cross-sectional descriptive research was undertaken in Indonesia among government servants who presently use BPJS Kesehatan services. Proposed modelling of insurance scheme were established as a solution bridging to be elaborated and implemented in the near future. Keywords : Employee Benefit, Health Insurance, Public Servants, Insurance Model